2023
DOI: 10.17977/um062v5i32023p300-309
|View full text |Cite
|
Sign up to set email alerts
|

Survei Kondisi Fisik Peserta Ekstrakurikuler Bolabasket di SMA Negeri 1 Pacet Mojokerto

Abstract: One of the prerequisites in an effort to improve athlete achievement in sports activities is to have good physical condition. SMA Negeri 1 Pacet has a basketball extracurricular activity where participants are required to master techniques and tactics and must pay attention to the physical condition of each individual in order to have an impact on good appearance. This study was conducted with the aim of knowing the physical condition of the basketball extracurricular participants at SMA Negeri 1 Pacet Mojoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…As research conducted by (Ahmad et al, 2023a) reported that the arm muscle strength of extracurricular basketball participants of State Senior High School 1 Pacet Mojokerto was in the good category at 33.33%. It is hoped that the coach will provide training that can increase the strength of the player's arm muscles, which will support technical ability and success in achieving victory when competing, because basketball is one of the games using hands.…”
Section: Description Of Physical Condition Of Center Positionmentioning
confidence: 91%
See 1 more Smart Citation
“…As research conducted by (Ahmad et al, 2023a) reported that the arm muscle strength of extracurricular basketball participants of State Senior High School 1 Pacet Mojokerto was in the good category at 33.33%. It is hoped that the coach will provide training that can increase the strength of the player's arm muscles, which will support technical ability and success in achieving victory when competing, because basketball is one of the games using hands.…”
Section: Description Of Physical Condition Of Center Positionmentioning
confidence: 91%
“…When viewed from the main task of the power forward position is to catch the bouncing ball from the ring both in defense and attack. In the defensive position this position is also tasked with blocking attacks from opponents and helping the center player get rebounds and score points from under the ring (Ahmad et al, 2023b). Based on these tasks, it is expected that the power forward position has good arm strength and leg muscles to support both defensive and offensive basketball games.…”
Section: Description Of Physical Condition Of Center Positionmentioning
confidence: 99%
“…Kemudian, penting adanya bagi setiap manusia mengetahui kondisi fisik dirinya sendiri. Peserta ekstrakurikuler olahraga pada umumnya harus mengetahui kondisi fisiknya masingmasing (Ahmad et al, 2023). Pelatih dalam ekstrakurikuler pada dasarnya harus mengetahui kondisi fisik atletnya (Candra et al, 2019).…”
Section: Pendahuluanunclassified